Structural ductility and embrittlement of fiber-reinforced shotcrete: Problems and solutions - Quinto Espinoza, Jim Kerri (2023)
In the Huanzalá Mine, the problems in the fiber-reinforced shotcrete (hereinafter SRF) were identified, the underground mining works present deterioration in the cracked shotcrete, therefore, the structural ductility and embrittlement of the steel and polymer SRF are analyzed.The initial deformations around the excavation are estimated with the RS2 software, which indicate that the SRF will present cracks that are monitored in the field (width and convergence); the energy absorption properties of steel and polymer SRF are obtained by laboratory tests. For steel fiber cases, the structural ductility after a crack drops steadily due to the change from ductile failure to brittle failure, for that reason, steel fibers were replaced by polymer fibers in SRF design, the energy absorption characteristics of the polymer SRF do not indicate any drop in capacity with increasing crack width and the effects of embrittlement are nil.Subsequently, the results achieved regarding the post-cracking behavior of a polymer SRF are support so that fissures and cracks are allowed and normalized in the Pallancata Mine.